The Effect of Integrity and Supervision on Work Discipline with Organizational Commitment as Mediator on Generation Z Police Non-Committed Officers at the Bengkulu Regional Police - Guspurwati, Hera; Wibowo, Ugung Dwi Ario; Abdul Rahman, Mohd Nazri; Ambari, Mahdi; Silawati, Endah (Dinasti International Journal of Education Management and Social Science, 2025)
Work discipline is critical for enhancing the performance and professionalism of police forces. This study investigates how integrity and supervision affect the work discipline of Generation Z non-commissioned officers (NCOs) at the Bengkulu Regional Police, using organizational commitment as a mediator. The urgency is underscored by a rise in disciplinary violations among Gen Z officers in 2024-2025. A quantitative approach using SEM-PLS was applied to data from 155 respondents, collected via validated instruments.The results show that organizational commitment is the strongest direct driver of work discipline (path coefficient: 0.898). Integrity significantly builds commitment (0.665) and exerts its main influence on discipline indirectly through this mediator (0.597). In contrast, the direct effects of integrity (0.096) and supervision (0.009) on discipline are negligible, though supervision also strengthens commitment (0.279) and has a meaningful indirect effect (0.250). The study concludes that for Generation Z officers, strengthening work discipline is best achieved by fostering organizational commitment, which is primarily shaped by integrity.Therefore, police management should implement integrity development programs and adopt supportive, humanistic supervision to enhance commitment and, consequently, discipline and overall performance.